Mdfi Promotes C2C12 Cell Differentiation and Positively Modulates Fast-to-Slow-Twitch Muscle Fiber Transformation - Huang, Bo; Jiao, Yiren; Zhu, Yifan; Ning, Zuocheng; Ye, Zijian; Li, Qing X.; Hu, Chingyuan; Wang, Chong (Frontiers in Cell and Developmental Biology, 2021)
Muscle development requires myoblast differentiation and muscle fiber formation. Myod family inhibitor (Mdfi) inhibits myogenic regulatory factors in NIH3T3 cells, but how Mdfi regulates myoblast myogenic development is still unclear. In the present study, we constructed an Mdfi-overexpression (Mdfi-OE) C2C12 cell line by the CRISPR/Cas9 system and performed RNA-seq on Mdfi-OE and wild-type (WT) C2C12 cells. The RNA-seq results showed that the calcium signaling pathway was the most significant. We also established the regulatory networks of Mdfi-OE on C2C12 cell differentiation and muscle fiber type transformation and identified hub genes. Further, both RNA-seq and experimental verification demonstrated that Mdfi promoted C2C12 cell differentiation by upregulating the expression of Myod, Myog, and Myosin. We also found that the positive regulation of Mdfi on fast-to-slow-twitch muscle fiber transformation is mediated by Myod, Camk2b, and its downstream genes, such as Pgc1a, Pdk4, Cs, Cox4, Acadm, Acox1, Cycs, and Atp5a1. In conclusion, our results demonstrated that Mdfi promotes C2C12 cell differentiation and positively modulates fast-to-slow-twitch muscle fiber transformation. These findings further our understanding of the regulatory mechanisms of Mdfi in myogenic development and muscle fiber type transformation. Our results suggest potential therapeutic targets for muscle- and metabolic-related diseases.